Pengajaran Berbicara Bahasa Inggris dengan Menggunakan Teknik Role-play di sebuah SMA di Bandung - Nendah Sari Indriani; Rahma Sakina (ELT in Focus, 2022)
The purposes of this study are to: (1) investigate how role-play technique is used in English speaking class, (2) to find out advantages of using role-play technique in teaching speaking from students’ and teacher’s perception, and (3) to figure out the difficulties that students and an English teacher encountered when using role-play technique in the classroom. The method used is qualitative with observation and interview as data collection techniques. The findings showed that the teacher carried out role-play technique with several stages such as delivering materials, dividing students into several groups to make a dialogue, students’ practicing the dialogue in their group, students’ performing the dialogue in front of the class, and evaluating students’ performance. Role-play technique provided some advantages. Firstly, it gave students opportunities to practice their speaking ability. Secondly, it increased students’ confidence to practice speaking in front of the classroom. Then, it improved students’ interests during the learning process. Fourth, it made students add more English vocabularies. Finally, students could communicate in English frequently with their friends so they could maintain their social relation with their peers. When using role-play technique, the students found difficulties related to pronunciation, word or sentence structure, lack of vocabulary, and memorizing the dialogue. The teacher found that role-play technique was time consuming, and it was hard to make sure the suitability of the material to the activities.